Co-expression of AGPS and AGPL genes encoded for AGPase from cassava to enhance starch accumulation in transgenic tobacco - Đoài, Nguyễn Văn; Hồng, Nguyễn Minh; Ngọc, Lê Thu; Thơm, Nguyễn Thị; Trọng, Nguyễn Đình; Trang, Vũ Huyền; Hường, Nguyễn Thị Thuý; Vân, Phạm Thị; Ngọc, Phạm Bích (Vietnam Journal of Biotechnology, 2016)
The AGPase (ADP-Glucose pyrophosphorylase) is one of the ubiquitous enzymes catalyzing the first step in starch biosynthesis. It plays an important role in regulation and adjusts the speed of the entire cycle of glycogen biosynthesis in bacteria and starch in plants. In higher plants, it is a heterotetramer and tetrameric enzyme consisting two large subunits (AGPL) and two small subunits (AGPS) and encoded by two genes. In this paper, both AGPS and AGPL genes were sucessfully isolated from cassava varieties KM140 and deposited in Genbank with accession numbers KU243124 (AGPS) and KU243122 (AGPL), these two genes were fused with P2a and inserted into plant expression vector pBI121 under the control of 35S promoter. The efficient of this construct was tested in transgenic N. tabacum. The presence and expression of AGPS and AGPL in transgenic plants were confirmed by PCR and Western hybridization. The starch content was quantified by the Anthrone method. Transgenic plant analysis indicated that that two targeted genes were expressed simultaneously in several transgenic tobacco lines under the control of CaMV 35S promoter. The starch contents in 4 analyzed tobacco transgenic lines displays the increase 13-116% compared to WT plants. These results indicated that the co-expression of AGPS and AGPL is one of effective strategies for enhanced starch production in plant. These results can provide a foundation for developing other genetically modified crops to increase starch accumulation capacity.